2023
DOI: 10.21203/rs.3.rs-2760537/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effects of Sensory Integration Interventions on Automatic Reinforcement Behaviors in Children with Autism Spectrum Disorders: A Single Subject Study

Abstract: Background Identifying successful interventions for children with persistent behaviors maintained by automatic reinforcement is quite challenging.Methods This study analyzed the effects of interventions based on sensory integration (SI) on the automatic reinforcement behavior of two preschool boys with Autism Spectrum Disorders(ASD). First, we performed a functional analysis to determine whether the challenging behaviors were maintained by automatic reinforcement. Next, two sensory integration intervention as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Therefore, it may be concluded that the regulatory behaviors they use are for the purpose of managing the information that is received from the senses. These regulatory behaviors may include clapping their hands, covering their ears to block out hearing, bouncing up and down, panicking, withdrawing when touched, avoiding specific textures and odors, and/or waving their fingers in front of their eyes (Pi et al, 2023). On the basis of these complicated sensory processing issues, there emerges a series of explainable cause‐effect correlations about how toddlers manage with their environment and how they stumble upon challenging behaviors (Iarocci & McDonald, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it may be concluded that the regulatory behaviors they use are for the purpose of managing the information that is received from the senses. These regulatory behaviors may include clapping their hands, covering their ears to block out hearing, bouncing up and down, panicking, withdrawing when touched, avoiding specific textures and odors, and/or waving their fingers in front of their eyes (Pi et al, 2023). On the basis of these complicated sensory processing issues, there emerges a series of explainable cause‐effect correlations about how toddlers manage with their environment and how they stumble upon challenging behaviors (Iarocci & McDonald, 2006).…”
Section: Introductionmentioning
confidence: 99%